Technology Acceptance Model (TAM) dan Theory of Planned Behavior (TPB), Apikasinya dalam Penggunaan Software Audit oleh Auditor - Juniarti Juniarti (The Indonesian Journal of Accounting Research, 2013)
This research intends to reveal factors that influence the audit software usage of the auditor. The models that used to explain  audit software usage are technology acceptance model (TAM) and theory of planned behavior (TPB). This research uses auditor as a unit analysis. Statistical tool that used in this research is Structural Equation Modelling (SEM) . Data  are analyzed by using statistical software LISREL 8.30.This research prove that software characteristic is the greatly factor that determine audit software  acceptance followed by organizational characteristic factor. Moreover this research also prove that software audit acceptance act as the factor that influence audit software usage. Eventhough  it is not the only factor, there is not enough evidence to refute this hypothesis.